IMPACT OF FISCAL POLICY ON THE ACTIVITIES OF INDIVIDUAL ENTREPRENEURS - R. G. Akhmadeev (Вестник университета)
Statistics on the amount of individual entrepreneur (registered and stopping one’s financial-economic activity) have been investigated. Systematization of scientific – practical methods for formation of the concept “optimum taxing load” has been carried out. In order to equalize the tax burden for individual entrepreneurs, applying both the general tax regime and a special one in the form of a simplified tax system, it has been offered to harmonize the definition of the object of the insurance premiums taxation with the current single tax when choosing the object of taxation “income, after deduction of expenses incurred”. Since the fixed payment in terms of payment of insurance premiums is payable regardless of the actual conduct of its own business for the calendar year, this proposal will allow us proportionately fulfill tax obligations to the budget.